What’s History Got to Do With It?: Reconsidering the Place of Historical Knowledge in Archival Work - Nesmith, Tom (Archivaria, 2004)
This article discusses the changing place of historical knowledge in archival work, particularly in Canada since the mid-twentieth century. The author begins by noting that knowledge of the history of one’s country or community was the centrepiece of the early professional identity of Canadian archivists between the late-nineteenth and mid-twentieth centuries, when most archivists saw themselves as historians. The article then discusses the circumstances which subsequently prompted serious questioning and sometimes rejection of historical knowledge as a key component of an archivist’s expertise and professional identity. The role of historical knowledge has thus been contested and problematic for many archivists across the recent intellectual history of the Canadian archival profession. The author then points to recent archival, intellectual, and societal trends which suggest that the pendulum is swinging back, not in a simple return to the past, when archivists were largely indistinguishable from academic historians, but toward appreciation of the central place of historical knowledge in the distinctive body of knowledge, research, and daily work of the new archival profession which has emerged over the last quarter century. RÉSUMÉ Cet article aborde l’évolution de la place du savoir historique dans la pratique archivistique, au Canada en particulier, depuis les années 1950. L’auteur commence en notant que la connaissance de l’histoire de son propre pays ou de sa propre communauté était au centre de l’identité professionnelle des archivistes canadiens entre la fin du 19e et le milieu du 20e siècles, alors que la plupart des archivistes se définissaient comme historiens. L’article commente ensuite les circonstances qui ont mené au questionnement et parfois au rejet du savoir historique comme composante-clé de l’expertise des archivistes et de leur identité professionnelle. Le rôle de la connaissance historique a donc été contesté et pose problème pour plusieurs archivistes au cours de l’histoire récente de la profession archivistique canadienne. Par une analyse des tendances récentes au niveau archivistique, intellectuel et sociétal, l’auteur suggère que le pendule effectue un retour vers l’arrière, non pas vers l’époque où les archivistes étaient indissociables des historiens, mais plutôt vers une valorisation de la place centrale du savoir historique au sein de l’ensemble particulier des connaissances, des recherches et des tâches quotidiennes de la nouvelle profession archivistique qui a émergé durant le dernier quart de siècle.